Control of VTOL vehicles with thrust-tilting augmentation. (February 2015) - Hua, Minh-Duc; Hamel, Tarek; Morin, Pascal; Samson, Claude
Abstract: An approach to the control of a VTOL vehicle equipped with complementary thrust-tilting capabilities that nominally yield full actuation of the vehicle's position and attitude is developed. The particularity and difficulty of the control problem are epitomized by the existence of a maximum tilting angle which forbids complete and decoupled control of the vehicle's position and attitude in all situations. This problem is here addressed via the formalism of primary and secondary objectives and by extending a solution previously derived in the fixed thrust-direction case. The proposed control design is also illustrated by simulation results involving a quadrotor UAV with all propeller axes pointing in the same monitored tilted direction.